Naval warfare a global history since 1860 - Black, Jeremy (Rowman & Littlefield Publishers, Inc., 2017)
Historian Jeremy Black traces naval warfare from the 1860s into the future. He focuses on the interplay of technological development, geopolitics, and resource issues to provide a dynamic account of strategy and warfare worldwide. Through a global frame, he assesses not only leading powers but all those involved in naval conflict.